Surface Charge Affecting Fluid–Fluid Displacement at Pore Scale. Issue 9 (2nd February 2022) - Kalde, Anna; Lippold, Sophia; Loelsberg, Jonas; Mertens, Ann‐Kathrin; Linkhorst, John; Tsai, Peichun Amy; Wessling, Matthias
Abstract: Efficiency in fluid–fluid displacement is drastically reduced by viscous fingering, limiting the overall effectiveness in enhanced oil recovery, membrane science, and lateral flow devices used in biomedical applications. Local instabilities at the fluid–fluid interface lead to finger‐like patterns when a less viscous fluid displaces an immiscible fluid of higher viscosity. This widely observed phenomenon in multiphase flow inside porous media is infamously intricate to control, especially for given geometry and viscosity ratio. The presented study uses a highly controlled microfluidic porous network structure with tailored ionic surface strength. The direct correlation of viscous fingering evolution on the porous structure's zeta potential at a pore‐scale level is demonstrated via polyelectrolyte coatings using a layer‐by‐layer technique. Displacement patterns are tuned from vigorous viscous fingering over stable displacement to corner flow events across a broad range of capillary numbers depending on the applied coatings. The experimental data show an increasing trend of oil recovery with increasing surface wettability, consistent with several previous findings. Furthermore, the results reveal that surface zeta potential correlates positively with recovery rate but negatively with the displacement stability quantified by the fractal dimension. These insights enable a more targeted porous media design to obtain optimal multiphase flow control. Abstract : The effect of apparent zeta potential on displacement patterns is studied systematically for oil displaced by water. Various surface coatings are experimentally fabricated to investigate viscous fingering patterns and recovery factors using microfluidics. Accurately tailored structure properties and high‐resolution imaging reveal the inherent correlation of structure zeta potential and fluid interface stability, helping to explain emerging macroscopic displacement effects.